Human Capital Development in the Strategy of Innovative Entrepreneurs: การพัฒนาทุนมนุษย์ด้านกลยุทธ์ของผู้ประกอบการเชิงนวัตกรรม - Hareebin, Yuttachai (Journal of Applied Economics and Management Strategy, 2020)
บทคัดย่อ การพัฒนาทุนมนุษย์ด้านกลยุทธ์ของผู้ประกอบการเชิงนวัตกรรมนับว่าเป็นความสามารถเชิงกลยุทธ์ขององค์การในรูปแบบหนึ่งที่มีความสำคัญอย่างยิ่งต่อความสำเร็จของผู้ประกอบการธุรกิจเนื่องจากทุกองค์การต้องมีการพัฒนากลยุทธ์ให้ทันต่อเหตุการณ์และการเปลี่ยนแปลงอย่างรุนแรง ดังนั้น เพื่อเป็นพื้นฐานของการพัฒนาองค์การโดยใช้รูปแบบความสามารถขององค์การที่เป็นความสามารถเชิงกลยุทธ์ ผู้เขียนได้ทำการศึกษาวรรณกรรมเกี่ยวกับแนวคิดการพัฒนาทุนมนุษย์และการวิเคราะห์การยกระดับเชิงกลยุทธ์ของผู้ประกอบการ เชิงนวัตกรรม โดยแบ่งการอธิบายไว้ 3 ประเด็น คือ 1) ศึกษาความสัมพันธ์ระหว่างทุนมนุษย์กับการยกระดับเชิงกลยุทธ์ขององค์การ 2) มุมมองการพัฒนาทุนมนุษย์ของผู้ประกอบการ และ 3) แนวคิดการยกระดับ กลยุทธ์ของผู้ประกอบการเชิงนวัตกรรม จากการทบทวนวรรณกรรมสรุปได้ว่า การพัฒนากลยุทธ์ดังกล่าวนั้น ผู้ประกอบการต้องมีการมุ่งเน้นความสัมพันธ์เชิงระบบที่รวมถึงการบูรณาการความสามารถองค์การด้านกลยุทธ์ อาทิ การมุ่งเน้นความเป็นผู้ประกอบการเชิงนวัตกรรม การจัดการห่วงโซ่คุณค่าแบบพลวัต การบริหารจัดการข้อมูลและสารสนเทศ การยกระดับรูปแบบการแข่งขันของธุรกิจ และการสร้างเครือข่ายธุรกิจ เป็นต้น โดยมีการมองกลยุทธ์เป็นกระบวนการการเรียนรู้เชิงกลยุทธ์และการบูรณาการทรัพยากรภายในให้สอดคล้องกับความท้าทายใหม่ที่เกิดขึ้นจากปัจจัยภายนอกและการตอบสนองต่อการเปลี่ยนแปลงได้อย่างมีประสิทธิภาพ ABSTRACT The study of human capital development in the strategy of innovative entrepreneurs is crucial to the success of entrepreneurs because every organization needs to develop a strategy to keep up to date on any serious situations in order to maintain a competitive advantage. Therefore, the basis for the development of the organization by using its capabilities as a strategic capability, the author investigated the literature on the concepts of human capital development and the analysis of the strategic leverage of innovative entrepreneurs divided into three issues: 1) the relationship of human capital and strategic upgrading; 2) the human capital development of entrepreneurs; and 3) the concept of upgrading the strategies of innovative entrepreneurs. Referring to the literature reviews, the study concluded that entrepreneurs need to focus on relationship-oriented systems and strategies as critical processes within the organization, such as focusing on being an innovative entrepreneur, dynamic value chain management, data and information management, and enhancing business competition pattern and creating business networks. The strategic policies should be integrated of internal resources to match the new challenges arising from external factors, responding to change and competing more effectively.